Epidemiology and risk factors for avascular necrosis in childhood systemic lupus erythematosus in a Taiwanese population - Hsin-Lin Tsai (Nature Portfolio, 2020)
Abstract Childhood-onset systemic lupus erythematosus (SLE) is associated with greater disease activity, more aggressive course, and high rates of organ damage. The prolonged use of corticosteroids in childhood SLE contributes to increased morbidity, including avascular necrosis (AVN). We conducted this retrospective study using claims data from the Taiwan National Health Insurance Research Database, enrolling 1,472 children with newly-diagnosed SLE between 2005 and 2013. The mean age at the diagnosis of SLE was 15.5 ± 3.3 years, and the female to male ratio was 6.2:1. Thirty-nine patients (2.6%) developed symptomatic AVN during a mean follow-up of 4.6 ± 2.5 years. In multivariate analysis, the risk of AVN was higher in the patients with a daily prednisolone dose between 7.5 mg and 30 mg (HR 7.435, 95% CI 2.882–19.178, p < 0.001) and over 30 mg (HR 9.366, 95% CI 2.225–39.418, p = 0.002) than in those with a dose ≤ 7.5 mg/day. In addition, AVN was inversely correlated with the use of hydroxychloroquine > 627 days (HR 0.335, 95% CI 0.162–0.694, p = 0.003). In conclusion, high daily doses of prednisolone were associated with a significant risk of AVN, whereas the use of hydroxychloroquine > 627 days conferred an advantage. We suggest that the judicious use of corticosteroids combined with hydroxychloroquine might be a promising preventive strategy for AVN.